2021
DOI: 10.1056/nejmoa2106567
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab in Children with Uncontrolled Moderate-to-Severe Asthma

Abstract: Among children with uncontrolled moderate-to-severe asthma, those who received add-on dupilumab had fewer asthma exacerbations and better lung function and asthma control than those who received placebo. (Funded by Sanofi and Regeneron Pharmaceuticals; Liberty Asthma VOYAGE ClinicalTrials.gov number, NCT02948959.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
153
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(163 citation statements)
references
References 21 publications
(30 reference statements)
6
153
0
4
Order By: Relevance
“…Indeed, ILC2s are a well-recognized component of a network of immune cells that contribute to allergy and asthma and, as such, are targets of multiple biologics currently approved or in advanced clinical trials for adults and, in some cases, adolescents, including those targeting IgE, IL-4, IL-13, IL-5, IL-33 and thymic stromal lymphopoietin 104 . Of note, recent data show effects of the anti-IL-4/anti-IL-13 drug dupilumab in ameliorating uncontrolled moderate-to-severe asthma in 6–11-year-old children 105 . By contrast, the pro-inflammatory functions of ILC2s are beneficial in certain cancers, where ILC2s can be targets for anti-PD1 therapy to improve tumour rejection, at least in mouse models 61 .…”
Section: Conclusion and Therapeutic Prospectsmentioning
confidence: 99%
“…Indeed, ILC2s are a well-recognized component of a network of immune cells that contribute to allergy and asthma and, as such, are targets of multiple biologics currently approved or in advanced clinical trials for adults and, in some cases, adolescents, including those targeting IgE, IL-4, IL-13, IL-5, IL-33 and thymic stromal lymphopoietin 104 . Of note, recent data show effects of the anti-IL-4/anti-IL-13 drug dupilumab in ameliorating uncontrolled moderate-to-severe asthma in 6–11-year-old children 105 . By contrast, the pro-inflammatory functions of ILC2s are beneficial in certain cancers, where ILC2s can be targets for anti-PD1 therapy to improve tumour rejection, at least in mouse models 61 .…”
Section: Conclusion and Therapeutic Prospectsmentioning
confidence: 99%
“…The Liberty Asthma Voyage trial was a phase 3, double-blind, randomized, and placebo-controlled study which lasted 52 weeks and evaluated the therapeutic effects of dupilumab in children (age: 6–11 years) with moderate-to-severe asthma ( Bacharier et al, 2021 ). Dupilumab was administered every 2 weeks as add-on biological therapy at doses of either 100 mg (body weight ≤30 kg) or 200 mg (body weight >30 kg).…”
Section: Therapeutic Effects Of Dupilumab In Severe Asthmamentioning
confidence: 99%
“…Dupilumab is also effective in cases with elevated FeNo in the absence of eosinophilia, suggesting an IL-13 role in this kind of patient ( 27 ). A recent trial reported the efficacy and safety of dupilumab in moderate to severe asthma patients aged 6–11 years ( 28 ).…”
Section: T2-high Treatmentsmentioning
confidence: 99%